the ideal of democratic citizenship in matthew lipman’s philosophy for children project - Mora Alonso, César Augusto; cruz rivera, bibiana judith (childhood & philosophy, 2024)
One of the fundamental ideas of Matthew Lipman’s Philosophy for Children Project is his conception of democratic citizenship, since it has the mission to promote and preserve the foundation of a higher-quality democracy, which represents much more than mere idea of government system or political regime. Indeed, democratic citizenship assumes this form of organization of society as a way of life, which should be understood as people’s actions being supportive and transformative, and that would be the result of the deployment of higher-order thinking skills. For that reason, it is not gratuitous that this proposal for philosophical education for childhood tends to the formation of reasonable citizens, inasmuch as this effort requires the propitiation of some conditions that encourage the development of the multidimensionality of thinking in classrooms; in this vein, the arrival towards a full and reconstructive democracy involves a comprehensive preparation in the communities of inquiry, in order to carry out the effective exercise of democratic citizenship. Therefore, the aim of this paper is to highlight the importance of this citizenship in Matthew Lipman’s works.